2020
DOI: 10.1038/s41467-020-16300-x
|View full text |Cite
|
Sign up to set email alerts
|

TFEB regulates murine liver cell fate during development and regeneration

Abstract: It is well established that pluripotent stem cells in fetal and postnatal liver (LPCs) can differentiate into both hepatocytes and cholangiocytes. However, the signaling pathways implicated in the differentiation of LPCs are still incompletely understood. Transcription Factor EB (TFEB), a master regulator of lysosomal biogenesis and autophagy, is known to be involved in osteoblast and myeloid differentiation, but its role in lineage commitment in the liver has not been investigated. Here we show that during de… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

3
24
0

Year Published

2020
2020
2023
2023

Publication Types

Select...
7
1

Relationship

1
7

Authors

Journals

citations
Cited by 36 publications
(27 citation statements)
references
References 76 publications
3
24
0
Order By: Relevance
“…These mice have increased fibrosis and develop liver cysts which mimic a polycystic liver and develop CCA-like phenotype. 121 These findings suggest that TFEB may play a crucial role in determining liver cell fate during development and regeneration, and may also contribute to CCA, which seems independent of its functions in lysosomal biogenesis.…”
Section: Volume_26 Number_4 October 2020mentioning
confidence: 86%
See 1 more Smart Citation
“…These mice have increased fibrosis and develop liver cysts which mimic a polycystic liver and develop CCA-like phenotype. 121 These findings suggest that TFEB may play a crucial role in determining liver cell fate during development and regeneration, and may also contribute to CCA, which seems independent of its functions in lysosomal biogenesis.…”
Section: Volume_26 Number_4 October 2020mentioning
confidence: 86%
“…119,120 In a recent study, Pastore et al reported that TFEB can drive liver progenitor cell (LPC) differentiation and promote the formation of ductular structures. 121 Among the different cell types in the liver, TFEB is highly expressed in biliary cells. TFEB drives the differentiation of LPC into the progenitor/cholangiocyte lineage while inhibiting hepatocyte differentiation during the mouse liver development or upon regeneration in response to injury.…”
Section: Volume_26 Number_4 October 2020mentioning
confidence: 99%
“…However, since AAV-Cre is non-integrating, the viral transgene is lost with cell division, essentially allowing the liver to be repopulated with Hmgcr+ hepatocytes over time. It is also possible that some of the regenerating cells are not hepatocyte-derived, an event that can happen in very severe cases of liver injury (31). Regardless of the cellular source of the Hmgcr+ hepatocytes, there is sufficient metabolic capacity to protect these animals from liver failure.…”
Section: Downloaded Frommentioning
confidence: 99%
“…Recombinant Adeno-associated viruses (AAV) are small non-integrating, non-enveloped, singlestranded DNA viruses that can deliver transgenes to the liver with high efficiency (29). AAV delivery of Cre recombinase is rapidly gaining popularity for inducible deletion of genes in the adult liver (30,31). AAV can also be used to deliver the Clustered regularly interspaced short palindromic repeats by guest, on November 6, 2020 www.jlr.org Downloaded from 6 (CRISPR)/Cas9 genome editing system, which can directly disrupt genes, thus bypassing the need to generate new floxed mouse models (32,33).…”
Section: Introductionmentioning
confidence: 99%
“…Cell differentiation is an indispensable process in development, growth and regeneration of multicellular organisms. In the liver, TFEB induces the differentiation of murine liver stem/progenitor cells into the progenitor/cholangiocyte lineage while inhibiting hepatocyte differentiation through upregulating Sox9, a marker of precursor and biliary cells [8] . In acute promyelocytic leukemia, autophagy is critical for the differentiation of leukemic blasts.…”
Section: Introductionmentioning
confidence: 99%